Salience in second language acquisition - Gass, Susan M.; Spinner, Patti 1973-; Behney, Jennifer (Second language acquisition research series, 2018)
"Salience in Second Language Acquisition brings together contributions from top scholars of second language acquisition (SLA) in a comprehensive volume of the existing literature and current research on salience. In the first book to focus exclusively on this integral topic, the editors and contributors define and explore what makes a linguistic feature salient in sections on theory, perpetual salience, and constructed salience. They also provide a history of SLA theory and discussion on its contemporary use in research. An approachable introduction to the topic, this book is an ideal supplement to courses in SLA, and a valuable resource for researchers and scholars looking for a better understanding of the subject."--Provided by publisher.